Impact of Regional Management Alternatives and Land Conversion on the Net Primary Productivity in Heilongjiang Province, China - Hao, Fanghua; Wang, Wenyan; Ouyang, Wei; Luan, Yun (Journal of Environmental Accounting and Management, 2026)
The Chinese government has initiated a set of ecological restoration projects to address aggravated environmental pollution and land degradation; among these projects the Grain for Green Project (GFGP) is the most renowned policy with a significant influence on land use and land cover change (LUCC) in China. The Net Primary Productivity (NPP) as a key index of ecosystem productivity, was studied to estimate the contribution of LUCC and management alternatives as human factors in Heilongjiang Province from 2001 to 2012. Carnegie–Ames–Stanford Approach (CASA) model was been utilized to simulate NPP during the study areas. The results showed that the LUCC from cropland to forest was the main type of land transformation induced by the GFGP, whereas the significant increase of the NPP occurred in forest, cropland and grassland between 2001 and 2007. Since 2007, the greatest rise of the total NPP occurred in the cropland with a rise of 12.6%, and the forest and grassland NPP slightly declined. The newly restored forests were located in the extremely frigid area at the junction or margin of mountains and plains where there is lack of supervision and the benefit of GFGP is difficult to observe in a short period. The temporal-spatial results of the NPP changes induced by human activities reflect the vital role that management practices play in the change of NPP compared with LUCC in Heilongjiang Province. Our analysis indicates that the fragile ecological environment of Heilongjiang Province has not changed fundamentally, and there is still a risk of cyclical fluctuations. As a result, scientific management alternatives in the unchanged land should be implemented and combined with restoration projects with middle- and long-term perspectives, such as logging limits in the forest, natural fire prevention and the improvement of fertilizer and irrigation practices. The Chinese government is initiating a new round of the GFGP, and the research results would be helpful in guiding the policy implementation in the local regions.